The Political Potential of Urban Informality in the Global North: A Rancièrian Perspective. Issue 2 (June 2022) - van de Pas, Niek; de Kort, David; Koster, Martijn; Meijl, Toon van
In recent years, a growing number of scholars have highlighted the presence of urban informality in the Global North. Although we applaud this development, we deplore that this body of literature is characterized by analytical ambiguity and fragmented discussions. More specifically, the literature often reduces or repudiates the political potential of urban informality by (a) integrating it into the formal, (b) mobilizing it for policy purposes, and/or (c) designating it as a "policy problem." In this article, we examine the existing literature and rethink the concept of urban informality by discussing it in relation to Jacques Rancière's distinction between "police" and "politics." This distinction enables us to highlight the political potential of urban informality in the Global North.